Cash waqf and mu'aqat waqf / Norain Husna Norlizal … [et al.] - Norlizal, Norain Husna; Md Rahim, Nur Auni Huda; Hasmuni, Nur Hidayah; Zahari, Nurul Ashikin; Zaihan Marican, Wan Nurul Balqis (2023)
An Islamic endowment of property to be held in trust and used for religious or charitable purposes is known as a waqf. In Islamic finance, this is a well-known idea where the donor (waqif) dedicates the assets (mawquf) to a particular charitable purpose. The assets are overseen by a custodian (mutawalli), and they are dedicated to the designated purpose indefinitely. Although Muslim jurists disagree on who is legally entitled to the assets after the endowment is finished, the assets cannot be used for purposes other than those specified, or be sold to settle a debt. Throughout Islamic history, waqf has been crucial to the socioeconomic development of the region by facilitating public access to healthcare, education, and other public services.